Pengaruh katalis bentonit terhadap produksi minyak pada pirolisis sampah plastik low density polyethylene - Rahmat Iman Mainil; azridjal aziz; Syahdi Fahala Banjarnahor (BKS-TM Indonesia, 2025)
Pyrolysis is the heating of plastic waste at high temperatures with or without oxygen, producing oil, gas, and carbon residue. The use of catalysts in the pyrolysis process can accelerate the conversion of plastics, resulting in better-quality oil. This study aims to examine the potential of oil produced from the pyrolysis of Low-Density Polyethylene (LDPE) plastic with the addition of bentonite clay catalyst as an alternative fuel. The pyrolysis process was carried out experimentally at a temperature of 450 °C with a residence time of 60 minutes, and variations of catalyst composition of 0%, 5%, 10%, 15%, and 20% were tested to obtain the optimum condition. The composition that produced the highest oil yield was then tested at lower temperatures of 350°C and 400 °C with the same residence time. The optimum composition of bentonite clay catalyst was 15% at 450 °C. Without the catalyst (0% composition), the oil yield was 54.2%, which increased to 66% from a total feedstock of 500 g, and when compared to the plastic mass of 425 g, the oil yield reached 82.5%. The density of the oil was 0.766 g/ml, the viscosity was 1.53 cP, and the calorific value was 11302.33 cal/g. LDPE pyrolysis oil with bentonite clay catalyst showed characteristics closer to diesel fuel and kerosene. Thus, LDPE pyrolysis oil has the potential to be used as an alternative substitute for diesel fuel in energy applications.